2005
DOI: 10.1143/jpsj.74.1362
|View full text |Cite
|
Sign up to set email alerts
|

Imprinting Memory into Paste and Its Visualization as Crack Patterns in Drying Process

Abstract: In the drying process of a paste, we can imprint a memory into the paste that determines how it will be broken in the future. That is, if we vibrate the paste before it is dried, it remembers the direction of the initial external vibration, and the morphology of the resultant crack patterns is determined solely by the memory of this direction. The morphological phase diagram of crack patterns and the rheological measurement of the paste show that this memory effect is induced by the plasticity of the paste.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
69
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(71 citation statements)
references
References 16 publications
(18 reference statements)
2
69
0
Order By: Relevance
“…Information about crack positions must be stored in the clay layer, across multiple wettings and dryings. A similar concept was demonstrated by Nakahara and Matsuo, 8 who vibrated slurries prior to drying them. The resulting cracks were largely co-aligned with the direction of vibration.…”
Section: Discussionsupporting
confidence: 57%
“…Information about crack positions must be stored in the clay layer, across multiple wettings and dryings. A similar concept was demonstrated by Nakahara and Matsuo, 8 who vibrated slurries prior to drying them. The resulting cracks were largely co-aligned with the direction of vibration.…”
Section: Discussionsupporting
confidence: 57%
“…We had confirmed that this memory lasts at least one month. 12) In that experiment, we set a container in a small box, poured a paste into the container, vibrated the container for a short time, and kept the container at rest for one month. Since the container was kept in a small box, the humidity inside the small box became soon saturated, and the paste was kept wet without drying for one month.…”
Section: Characteristic Time For the Memory Effectsmentioning
confidence: 99%
“…[9][10][11] Recently, it has been reported that paste remembers the direction of external fields and the morphology of desiccation cracks can be controlled by memory effects of paste. [12][13][14] If we mix powder with water, pour the mixture into a container to make a thin layer, and dry it at a room temperature, desiccation cracks emerge with characteristic sizes of these fragments proportional to the depth of the mixture. [15][16][17][18] When the mixture contains a lot of water, it can be regarded as a viscous Newtonian fluid, and we usually get isotropic and cellular desiccation crack patterns.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations